Methylene blue modulates transendothelial migration of peripheral blood cells. - Isabella Werner (Public Library of Science (PLoS), 2013)
Vasoplegia is a severe complication after cardiac surgery. Within the last years the administration of nitric oxide synthase inhibitor methylene blue (MB) became a new therapeutic strategy. Our aim was to investigate the role of MB on transendothelial migration of circulating blood cells, the potential role of cyclic cGMP, eNOS and iNOS in this process, and the influence of MB on endothelial cell apoptosis. Human vascular endothelial cells (HuMEC-1) were treated for 30 minutes or 2 hours with different concentrations of MB. Inflammation was mimicked by LPS stimulation prior and after MB. Transmigration of PBMCs and T-Lymphocytes through the treated endothelial cells was investigated. The influence of MB upon the different subsets of PBMCs (Granulocytes, T- and B-Lymphocytes, and Monocytes) was assessed after transmigration by means of flow-cytometry. The effect of MB on cell apoptosis was evaluated using Annexin-V and Propidium Iodide stainings. Analyses of the expression of cyclic cGMP, eNOS and iNOS were performed by means of RT-PCR and Western Blot. Results were analyzed using unpaired Students T-test. Analysis of endothelial cell apoptosis by MB indicated a dose-dependent increase of apoptotic cells. We observed time- and dose-dependent effects of MB on transendothelial migration of PBMCs. The prophylactic administration of MB led to an increase of transendothelial migration of PBMCs but not Jurkat cells. Furthermore, HuMEC-1 secretion of cGMP correlated with iNOS expression after MB administration but not with eNOS expression. Expression of these molecules was reduced after MB administration at protein level. This study clearly reveals that endothelial response to MB is dose- and especially time-dependent. MB shows different effects on circulating blood cell-subtypes, and modifies the release patterns of eNOS, iNOS, and cGMP. The transendothelial migration is modulated after treatment with MB. Furthermore, MB provokes apoptosis of endothelial cells in a dose/time-dependent manner.